POLITENESS STRATEGIES IN UZBEK AND ENGLISH: A CROSS- LINGUISTIC PRAGMATIC STUDY - Abdullaeva Gulkhayo Ulugbekovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Politeness is a fundamental aspect of human communication, reflecting social norms, cultural values, and interpersonal relationships. This paper investigates politeness strategies in Uzbek and English, focusing on how speakers convey respect, make requests, and perform speech acts in context. Uzbek, as a language with rich morphological markers and honorific forms, contrasts with English, which relies on modal verbs, hedging, and indirect phrasing. Through comparative analysis, the study highlights the influence of culture on pragmatic choices, identifies patterns of directness and indirectness, and demonstrates how linguistic structures shape communication strategies. The findings contribute to cross-linguistic understanding and provide insights for second-language teaching and intercultural communication.